Sustainability of Public-Private Dialogue Initiatives : Practical Note to Ensure the Sustainability of Dialogue Partnerships - Herzberg, Benjamin; Sisombat, Lili (World Bank, Washington, DC, 2016)
This practical notes series is devised as a how-to guide that captures the evolution of Public Private Dialogues (PPD) and the challenges faced by practitioners since the first PPD handbook was published in 2006. It considers the varied and evolving forms of PPD, the contexts in which PPD is most effective, and its processes of implementation and sustainability. The design, implementation, and challenges associated with investment climate, competitiveness, and sector-specific PPDs are discussed, as well as an updated methodology for the monitoring and evaluation of PPDs. The series further provides an updated “PPD Charter of Good Practice” in Annex I that reflects practice modifications and improvements since being first elaborated at the 2006 Paris Global PPD Workshop. The series takes the Charter’s principles as its base, and expands on them with practical advice and recommendations. It comprises five practical notes: PPD Practical Note 1 – Sustainability of PPDs: This note focuses on the life span of PPDs and the challenge of sustainability. This note considers how PPDs can achieve long-term operational, financial and mandate sustainability.